A STUDY ON THE FUNDAMENTAL COMPONENTS AND SIGNIFICANCE OF MIZO TRADITIONAL FESTIVALS - LALCHHANHIMA (Innovare Journal of Social Sciences, 2021)
The traditional Mizo had various community feasts and celebrations, which were performed at specific time and period of the year. The three principle celebrations are Chapchar Kut (celebration of spring), Mim Kut (celebration performed when the yields other than paddy is first procured), and Pawl Kut (celebration of harvest). The Mizo adored social gathering and bustles, and likewise, Kut was a typical element of their public activity. Here we will look at into what the traditional Mizo had thought about fundamental components for festivity of their celebrations.